Răspunsuri

2014-04-26T13:24:12+03:00
Construim ED⊥ AC

DD'⊥ (ABCD)            T3
ED⊥ AC                  ⇒    D'E⊥AC
ED,AC⊂(ABCD)

Construim DF⊥D'E
D'E
⊥AC                  R2T3
DE⊥AC                  ⇒DF⊥(D'AC)⇒d(D,(D'AC))=DF
DF⊥D'E
D'E,AC
⊂(D'AC)

In ΔACD:
Din teorema lui Pitagora⇒AD²+CD²=AC²
                                     12²+(4√3)²=AC²
                                     144+48=AC²
                                     192=AC²
                                     AC=8√3cm
 T.h.⇒DE=AD×CD/AC=12×4√3/8√3=48√3/8√3=6cm
In ΔD'DE:
Di teorema lui Pitagora⇒D'E²=D'D²+DE²
                                   D'E²=(6√3)²+6²
                                   D'E²=108+36=144
                                  ⇒D'E=12cm
T.h.⇒DF=DE×D'D/D'E=6×6√3/12=36√3/12=3√3 cm
⇒d(D,(D'AC))=3√3cm